AGAINST THE VALIDITY OF THE CLOSED SYSTEM MODEL FOR CALCULATING OSMOTIC PRESSURE (Journal of Sciences, Islamic Republic of Iran)
This paper criticizes the model and the new definition for osmotic pressure given by Parsafar et al. [J. Sci. I. R. Iran, Vol. 10, No. 4, 233 (1999)]. The model is a closed system containing 1 kg of solvent plus m mole of solute at constant temperature and under pressure P0 + ? where P0 is the standard pressure and ? is the osmotic pressure of the corresponding m molal solution. While the total number of moles, temperature and pressure of the system are specified, the volume of the system has also been specified. The volume of the solution under pressure P0 + ? is claimed to be the same as the volume of 1 kg of pure solvent under the standard pressure P0. The present work shows that the two volumes can not be the same and their difference is not negligible. The use of an equation of state to calculate osmotic pressure and activity by Parsafar et al. has also been questioned.